2014
DOI: 10.5588/ijtld.13.0417
|View full text |Cite
|
Sign up to set email alerts
|

The first population-based national tuberculosis prevalence survey in Ethiopia, 2010-2011

Abstract: We found that the TB burden was lower than previously thought, which may indicate better programme performance. However, a high proportion of TB among young persons suggests that TB is circulating in the community and that there is a need for more efforts to limit the spread of TB disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
151
7
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(174 citation statements)
references
References 4 publications
14
151
7
2
Order By: Relevance
“…For example, in USA compared to the general population, homeless individuals had an approximately tenfold increase in TB prevalence [33]. Extrapolation of this study finding also indicated that about 4.67 times higher burdens of smear positive PTB in homeless individuals than the general population (108/100,000) in Ethiopia [34]. This study point prevalence of smear positive PTB is comparable to a study conducted in Greater London (780/100,000) [32].…”
Section: Discussionmentioning
confidence: 74%
“…For example, in USA compared to the general population, homeless individuals had an approximately tenfold increase in TB prevalence [33]. Extrapolation of this study finding also indicated that about 4.67 times higher burdens of smear positive PTB in homeless individuals than the general population (108/100,000) in Ethiopia [34]. This study point prevalence of smear positive PTB is comparable to a study conducted in Greater London (780/100,000) [32].…”
Section: Discussionmentioning
confidence: 74%
“…Experts in mapping and epidemiology were involved in harmonizing the two protocols and resolved differences between the two approaches. The planning drew on experience from previous large scale studies in the country such as the Malaria Indicators Survey [31, 32], previous LF mapping [23] and the national tuberculosis survey [32]. After the final protocol was developed, disease specific training manual and standard operating procedure (Additional file 1) for conducting the mapping were developed.…”
Section: Resultsmentioning
confidence: 99%
“…4 A more proactive strategy, such as community-based screening, can identify large numbers of undiagnosed prevalent TB cases, as demonstrated by epidemiologic studies in China and other high-burden countries. 2,5–7 One epidemiologic study conducted at eight sites in China compared passive vs. active case finding (ACF), and found TB prevalence obtained through active screening was significantly higher than TB registry data of other townships in the same region over the same period. 8 Based on a review of available evidence, the World Health Organization (WHO) issued active case screening recommendations in 2013.…”
mentioning
confidence: 99%